2011
DOI: 10.1016/j.actamat.2011.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Coarsening by network restructuring in model nanoporous gold

Abstract: Using atomistic modeling, we show that restructuring of the network of interconnected ligaments causes coarsening in a model of nanoporous gold. The restructuring arises from the collapse of some ligaments onto neighboring ones and is enabled by localized plasticity at ligaments and nodes. This mechanism may explain the occurrence of enclosed voids and reduction in volume in nanoporous metals during their synthesis. An expression is developed for the critical ligament radius below which coarsening by network r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 45 publications
6
58
1
Order By: Relevance
“…Although the surface diffusion is possibly responsible for the pore/ ligament structure evolution annealed at temperature below 200°C [32], it is not sufficient to explain the experimental observations such as large volume reduction [10] and encased voids in ligaments [33]. Most recently, Kolluri and Demkowicz [34] reported that the ligament coarsening may arise from the volume diffusion by the collapse of neighboring ligaments onto each other. By scanning transmission electron microscopy, the surface diffusion and grain boundary diffusion (volume diffusion) are observed at intermediate and higher temperature, respectively [32].…”
Section: Methodsmentioning
confidence: 95%
“…Although the surface diffusion is possibly responsible for the pore/ ligament structure evolution annealed at temperature below 200°C [32], it is not sufficient to explain the experimental observations such as large volume reduction [10] and encased voids in ligaments [33]. Most recently, Kolluri and Demkowicz [34] reported that the ligament coarsening may arise from the volume diffusion by the collapse of neighboring ligaments onto each other. By scanning transmission electron microscopy, the surface diffusion and grain boundary diffusion (volume diffusion) are observed at intermediate and higher temperature, respectively [32].…”
Section: Methodsmentioning
confidence: 95%
“…The restructuring arises from the collapse of some ligaments onto neighboring ones and is enabled by localized plasticity at ligaments and nodes. This mechanism may also explain the occurrence of enclosed voids and macroscopic shrinkage in np-Au during the dealloying [93]. It is also suggested a critical ligament radius below which coarsening by network restructuring may occur spontaneously, setting a lower limit to the ligament dimensions of nanoporous metals.…”
Section: Volume Shrinks and Surface Cracksmentioning
confidence: 93%
“…Since the original crystal lattice is maintained after the dealloying, it is suggested that plastic deformation, which could arise by homogeneous slip in small ligaments or by climb of lattice dislocations, provides the most obvious mechanism. Recently, using a atomistic modeling, Kolluri and Demkowicz [93] showed that restructuring of the network of interconnected ligaments causes coarsening in a model of np-Au. The restructuring arises from the collapse of some ligaments onto neighboring ones and is enabled by localized plasticity at ligaments and nodes.…”
Section: Volume Shrinks and Surface Cracksmentioning
confidence: 99%
“…Nanoporous gold is an emerging material that attracted significant attention for its unusual catalytic and optical performance, [13][14][15][16] as well as its versatility in studying structure-property relationships for numerous applications. [17][18][19][20][21] Np-Au is typically synthesized by selective dissolution of silver from a silver-rich gold-silver alloy, where surface diffusion of gold atoms lead to a bicontinuous open-pore morphology. 22 This process, also known as dealloying, produces ~70% porosity and pore/ligament sizes in the range of tenths of nanometers.…”
Section: Introductionmentioning
confidence: 99%